The Arrow Domination of Some Generalized Graphs - Dipshi,; Mehra, Seema (Communications in Mathematics and Applications, 2023)
The aim of this article is to apply the concept of arrow domination defined by Radhi et al. (The arrow domination in graphs, International Journal of Nonlinear Analysis and Applications 12(1) (2021), 473 – 480) on some generalized graphs like Friendship graph or Fan graph, Gear graph, Helm graph, Flower graph, Sunflower graph, Triangular snake graph, Double triangular snake graph, Petersen graph, Dragon graph, Lollipop graph and Barbell graph.